Identification of potential host plant mimics of CLAVATA3/ESR (CLE)-like peptides from the plant-parasitic nematode Heterodera schachtii - WANG, JIANYING; REPLOGLE, AMY; HUSSEY, RICHARD; BAUM, THOMAS; WANG, XIAOHONG; DAVIS, ERIC L; MITCHUM, MELISSA G (Molecular plant pathology, 2011)
In this article, we present the cloning of two CLAVATA3/ESR (CLE)-like genes, HsCLE1 and HsCLE2, from the beet cyst nematode Heterodera schachtii, a plant-parasitic cyst nematode with a relatively broad host range that includes the model plant Arabidopsis. CLEs are small secreted peptide ligands that play important roles in plant growth and development. By secreting peptide mimics of plant CLEs, the nematode can developmentally reprogramme root cells for the formation of unique feeding sites within host roots for its own benefit. Both HsCLE1 and HsCLE2 encode small secreted polypeptides with a conserved C-terminal CLE domain sharing highest similarity to Arabidopsis CLEs 1-7. Moreover, HsCLE2 contains a 12-amino-acid CLE motif that is identical to AtCLE5 and AtCLE6. Like all other plant and nematode CLEs identified to date, HsCLEs caused wuschel-like phenotypes when overexpressed in Arabidopsis, and this activity was abolished when the proteins were expressed without the CLE motif. HsCLEs could also function in planta without a signal peptide, highlighting the unique, yet conserved function of nematode CLE variable domains in trafficking CLE peptides for secretion. In a direct comparison of HsCLE2 overexpression phenotypes with those of AtCLE5 and AtCLE6, similar shoot and root phenotypes were observed. Exogenous application of 12-amino-acid synthetic peptides corresponding to the CLE motifs of HsCLEs and AtCLE5/6 suggests that the function of this class of CLEs may be subject to complex endogenous regulation. When seedlings were grown on high concentrations of peptide (10 µm), root growth was suppressed; however, when seedlings were grown on low concentrations of peptide (0.1 µm), root growth was stimulated. Together, these findings indicate that AtCLEs1-7 may be the target peptides mimicked by HsCLEs to promote parasitism.